Acyl CoA-binding protein in brown adipose tissue acts as a negative regulator of adaptive thermogenesis - Blasco-Roset, Albert; Quesada-López, Tania; Mestres-Arenas, Alberto; Villarroya, Joan; Godoy-Nieto, Francisco J.; Cereijo, Rubén; Rupérez, Celia; Neess, Ditte; Færgeman, Nils J.; Giralt, Marta; Planavila, Anna; Villarroya, Francesc (Molecular metabolism (Germany), 2025)
Defective activity of brown adipose tissue (BAT) is linked to obesity and cardiometabolic diseases. While much is known regarding the biological signals that trigger BAT thermogenesis, relatively little is known about the repressors that may impair BAT function in physiological and pathological settings. Acyl CoA-binding protein (ACBP; also known as diazepam binding inhibitor, DBI) has intracellular functions related to lipid metabolism and can be secreted to act as a circulating regulatory factor that affects multiple organs. Our objective was to determine the role of ACBP in BAT function. Experimental models based on the targeted inactivation of the Acbp gene in brown adipocytes, both in vitro and in vivo, as well as brown adipocytes treated with recombinant ACBP, were developed and analyzed for transcriptomic and metabolic changes. ACBP expression and release in BAT are suppressed by noradrenergic cAMP-dependent signals that stimulate thermogenesis. This regulation occurs through gene expression modulation and autophagy-related processes. Mice with targeted ablation of Acbp in brown adipocytes exhibit enhanced BAT thermogenic activity and protection against high-fat diet-induced obesity and glucose intolerance; this is associated with BAT transcriptome changes, including upregulation of BAT thermogenesis-related genes. Treatment of brown adipocytes with exogenous ACBP suppresses oxidative activity, lipolysis, and thermogenesis-related gene expression. ACBP treatment inhibits the noradrenergic-induced phosphorylation of p38 MAP-kinase and CREB, which are major intracellular mediators of brown adipocyte thermogenesis. The ACBP system acts as a crucial auto regulatory repressor of BAT thermogenesis that responds reciprocally to the noradrenergic induction of BAT activity. [Display omitted] •ACBP expression and release in BAT are suppressed by thermogenic stimuli.•Genetic ablation of Acbp in BAT protects against obesity and glucose intolerance.•ACBP impairs thermogenesis-related metabolism and gene expression in brown adipocytes.•ACBP system is an auto-regulatory repressor of BAT thermogenesis.